[Retracted] The Prototype of the Reading Learning Application uses Animated images on Android with the Black Box Testing Method - Buntoro, Ghulam Asrofi; Astuti, Indah Puji; Ariyadi, Dwiyono (Jurnal Informatika Universitas Pamulang, 2021)
This article has been withdrawn by the author (Ghulam Asrofi Buntoro) via WhatsApp message (+62 852-3507-????) on 20 August 2021 at 14:23. He stated that the article "The Prototype of the Reading Learning Application uses Animated images on Android with the Black Box Testing Method" written by Ghulam Asrofi Buntoro, Indah Puji Astuti, and Dwiyono Ariyadi had been published in another journal.Â Artikel ini telah ditarik kembali oleh penulis (Ghulam Asrofi Buntoro) melalui pesan WhatsApp (+62 852-3507-????) pada tanggal 20 Agustus 2021 jam 14:23. Dia menyatakan bahwa artikel dengan judul "The Prototype of the Reading Learning Application uses Animated images on Android with the Black Box Testing Method" yang ditulis oleh Ghulam Asrofi Buntoro, Indah Puji Astuti, dan Dwiyono Ariyadi telah diterbitkan di jurnal lain.